Molecular Prevalence and Causes of Hepatitis B Virus Infection in District Bannu Khyber Pakhtunkhwa, Pakistan - Hafsa Tawab; Tanzila Khalil (Global Journal of Clinical Virology - Peertechz Publications, 2021)
Hepatitis B Virus (HBV) infection is a major health problem in the developing countries counting Pakistan. This study aimed to examine causes and molecular prevalence of HBV in district Bannu Khyber Pakhtunkhwa province, Pakistan. For the diagnosis of anti HBV antibodies a total of 500 blood sample were collected from gender patients, (300 males and 200 females) were screened, directed by clinicians of HBV in the Khalifa Gull Nawaz Teaching Hospital Bannu. All the individuals were aged between 01-60 years categorized into three groups. Out of which 78 (26%) males and 48(24%) females were reported positive for anti HBV. Individuals including 75 (25%) males and 47 (23.5%) females were found positive for HBV DNA while the remaining 4patients including 2 males and 2 female were found negative. Sex-wise distribution of HBV infection shows that as compared to female population 47 (23.5%) male population was more infected 75 (25%), the higher prevalence rate was found in female as compare to male. The present study also observed prevalence of HBV age wise from 1 to 60 years. The lowest HBV rate is found in age group of 1-20.This may be due to the reason that they have a strong immune system and also have a minimum contact with a factors transmitted HBV such as a barber contact, drug abuse, tattooing and piercing, surgery, and blood transfusion. Moderate rate is found in age group 21-40.This is due to the fact that these people have weak immune response and high contact with risk factors associates with HBV than children. Highest prevalent rate found in age group of 41-60 due to weak immune system and lack of awareness. Extensive vaccination and other preventive measures should be taken to stop the spread of this dreadful disease in the general population of District Bannu KP Pakistan.